Digit Ratio (2D:4D): A Biomarker for Prenatal Sex Steroids and Adult Sex Steroids in Challenge Situations - Manning, John; Kilduff, Liam; Cook, Cristian; Crewther, Blair; Fink, Bernhard (Frontiers in Endocrinology, 2014)
Digit ratio (2D:4D), which denotes the relative length of the 2nd and 4th digits, is considered to be a biomarker of the balance between foetal testosterone and oestrogen in a narrow window of early ontogeny. Evidence from this assertion is derived from direct and indirect measures of prenatal hormonal exposure (in experimental animals, via amniotic fluid samples and in the study of sex-typical traits) in relation to 2D:4D. In contrast, the relationships between 2D:4D and levels of sex steroids in adults are less clear, as many correlational studies of 2D:4D and adult sex steroids have concluded that there is little in the way of associations. Here we suggest that in order to understand the link between 2D:4D and sex hormones one must consider both foetal organising and adult activating effects of testosterone and oestrogen. In particular, we hypothesise that 2D:4D correlates with early organising effects on the endocrine system that moderate activating effects in adulthood. We argue that this can be especially observed through an elevated propensity in adults to produce testosterone in “challenging” conditions such as aggressive and sexual encounters. We discuss this refinement of the 2D:4D paradigm in relation to the links between 2D:4D and sports performance, and aggression.